Faktor – Faktor Yang Mempengaruhi Stunting Pada Anak Dan Balita Di Desa Mangunjaya Kecamatan Bantar Gadung - Hesri Mintawati; Dana Budiman; Suprapto; Paikun (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2022)
The prevalence of stunting in Sukabumi Regency is at 6.9 percent based on data received until December 2020, this number is decreasing when compared to several years ago, based on Riskesdas data in 2018, the prevalence of stunting in Sukabumi Regency is 41.35 percent. Sukabumi Regency has 365 villages where the attention is 20 villages that are the goal of researchers in conducting research, therefore it is necessary to use a methodology in research using observation and interviews. With the steps that must be taken together with the Government and the Community, where this community service aims to solve problems in handling stunting in 20 villages in Sukabumi Regency with two alternatives, namely planning to provide donations in the form of nutritious rice. The next plan is to provide socialization to posyandu officers about stunting which focuses on 20 villages that are fostered villages, then the second plan is carried out together with posyandu officers in 20 villages experiencing stunting to minimize stunting in 2025. The Sukabumi government is targeting zero new stunting according to the President's instructions